Delirium risk in non-surgical patients: systematic review of predictive tools. (July 2019) - Dylan, Flaws; Byrne, Gerard; Mudge, Alison M
Highlights: Clinical practice guidelines recommend screening inpatients for risk of delirium. Our systematic review found 22 risk screening tools in nonsurgical inpatient samples. Most validated tools are in older medical or geriatric patients. Varied risk factors and inconsistent definitions make comparison difficult. Practical application of risk screening requires further research. Abstract: Objective: Delirium is a common, serious condition associated with poor hospital outcomes. Guidelines recommend screening for delirium risk to target diagnostic and/or prevention strategies. This study critically reviews multicomponent delirium risk prediction tools in adult non-surgical inpatients. Study design: Systematic review of studies incorporating at least two clinical factors in a multicomponent tool predicting risk of delirium during hospital admission. Derivation and validation studies were included. Study design, risk factors and tool performance were extracted and tabulated, and study quality was assessed by CHARMS criteria. Data sources: PubMed, Embase, PsycINFO, and Cumulative Index to Nursing Health Literature (CINAHL) to 11 th March 2018. Data synthesis: 22 derivation studies enrolling 38, 874 participants (9 with a validation component) and 4 additional validation studies were identified, from a range of ward types. All studies had at least moderate risk of bias. Older age and cognitive, functional and sensory impairment were important predisposing factors. Precipitating risk factors included infection, illness severity, renal and electrolyte disturbances. Tools mostly did not differentiate between predisposing and precipitating risk factors mathematically or conceptually Most tools showed fair to good discrimination, and identified more than half of older inpatients at risk. Conclusions: Several validated delirium risk prediction tools can identify patients at increased risk of delirium, but do not provide clear advice for clinical application. Most recommended cut-points are sensitive but have low specificity. Implementation studies demonstrating how risk screening can better direct clinical interventions in specific clinical settings are needed to define the potential value of these tools.